Implementation of Science-Physics Learning Based on Coastal Fisherman Activities to Improve Students' Scientific Literacy Abilities - Putri, Neysa Javita; Zulirfan, Z; Sahal, Muhammad (Journal of Indonesian Science Teachers, 2024)
Science education in Indonesia faces challenges in increasing students' scientific literacy, especially at the secondary level. One of the problems faced is the lack of student involvement in science learning relevant to their context. This research aims to improve the scientific literacy skills of class VIII students at SMPN 4 Dumai by applying science-physics learning based on coastal fishermen's activities on work and energy material. The research method used is experimental research using 2 class groups, namely the experimental and control classes. The population of this research was class VIII students at SMPN 4 Dumai. The instrument used to collect data was the results of students' scientific literacy ability tests. The results of the research show that the application of science-physics learning based on coastal fishing activities results in higher scientific literacy abilities and increases significantly. Apart from that, the application of this learning can increase students' interest in linking their daily lives with learning material. Science-physics learning based on coastal fishing activities is effective in increasing students' scientific literacy in work and energy material for class VIII junior high school students.